A doctoral journey – In the steps of J Rodney Turner. Issue 1 (January 2018) - Crawford, Lynn
Abstract: Interest in project related doctorates is increasing, and Dr J Rodney Turner has led the way as a supervisor, encouraging and guiding prospective doctoral candidates while extending the field of project studies often in new directions. This short paper offers insights into the doctoral journey from the perspective of both student and supervisor as it follows the experience of a doctoral candidate supervised by Dr Turner. The aim is to celebrate Dr Turner's contribution as a project researcher and doctoral supervisor and to offer useful guidance to doctoral supervisors following in his footsteps and to those interesting in embarking on a doctoral journey.